2021
DOI: 10.1161/atvbaha.120.315786
|View full text |Cite
|
Sign up to set email alerts
|

Anticytomegalovirus CD4 + T Cells Are Associated With Subclinical Atherosclerosis in Persons With HIV

Abstract: Objective: Persons with HIV have doubled the risk of developing cardiovascular disease compared with the general population. A persistent and heightened immune response to cytomegalovirus coinfection may be one contributing factor, but the relationship between cytomegalovirus replication, virus-specific immune cells, and plaque burden is unclear. Approach and Results: We assessed the relationship between CD4 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Residual cardiovascular risk in PWH after adjustment for CVD risk is thought to be caused by multiple factors including inflammation. 28 , 30 A persistent HIV viral reservoir, its effect on CD4 T‐cell counts, and other chronic viral co‐infections may be important. The relationships between mean corCSA, ART duration, and CD4 T cells suggest that HIV status and the effect of the virus on CD4 T cells may contribute to coronary arterial remodeling in PWH and CVD risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residual cardiovascular risk in PWH after adjustment for CVD risk is thought to be caused by multiple factors including inflammation. 28 , 30 A persistent HIV viral reservoir, its effect on CD4 T‐cell counts, and other chronic viral co‐infections may be important. The relationships between mean corCSA, ART duration, and CD4 T cells suggest that HIV status and the effect of the virus on CD4 T cells may contribute to coronary arterial remodeling in PWH and CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…All plasma cytokines were measured using a standard multiple immunoassay panel (MesoScale, Rockville, MD) as previously published. 28 …”
Section: Methodsmentioning
confidence: 99%
“…CMV is a herpesvirus that co-evolved with mammals and infects many individuals at a young age, and CMV is highly prevalent in some groups including adult PWH (14,15). Growing evidence suggests that anti-CMV T cell responses have a role in metabolic dysregulation in both animal models (16) and humans (17)(18)(19)(20)(21)(22). CMV-seropositivity has been shown to predict severe non-AIDSrelated illnesses and is an independent risk factor for cardiovascular and cerebrovascular disease in PWH (8,23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies from our group suggest that an increase in CMVspecific CD4 + T cells in PWH may serve as a novel marker of metabolic and cardiovascular disease risk. We previously showed that adipose tissue CD4 + T cells co-expressing CX3CR1, GPR56, and CD57 (termed 'CGC + ' cells), a surface marker combination suggestive of antiviral activity, increased with progressive glucose intolerance (26) and with carotid plaque burden in PWH (18). Furthermore, we showed that CMV-specific CD4 + T cells that recognized an immunodominant peptide epitope (DYSNTHSTRYV from glycoprotein B (gB)) restricted through HLA-DR7 were predominantly CGC + (17,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation